Pembelajaran Gramatika Bahasa Arab Menggunakan Metode Bernyanyi Dengan Buku Irama Nahwu Di Asrama Darussibyan Assunniyyah - Nafsah, Nor Holis bin; Rosyadi, Hamdan; Khoiroh, Immatul (An-Nuqthah, 2024)
This assistance aims to maximize learning of Arabic grammar using the singing method with the Nahwu rhythm book in improving the reading skills of students at the Darussibyan As-sunniyyah Kencong-Jember boarding school. The application of this method is a breakthrough, so that learning Arabic grammar feels easy and fun. It is hoped that the Darussibyan boarding school students can easily memorize the Nahwu Rhythm text and understand the explanation of the contents of the Nahwu Rhythm book, and in turn it will be easier for them to understand the basics of reading the Yellow Book. The type of research used in this research is a qualitative method. This research concludes that the method of singing with the Nahwu rhythm book makes it easier for students to learn Arabic grammar and improves their ability to understand Arabic grammar, as a basis for reading books at the Darussibyan As-sunniyyah Kencong-Jember dormitory